Effect of Temperature and Nickel Concentration on the Electrical and Dielectric Properties of Polyethylene-Nickel Composites - A. Naeem, Ghassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of temperature range from 298 K to 348 K and volume filler content Ñ„ on electrical properties of polyethylene PE filled with nickel Ni powders has been investigated. The volume electrical resistivity V ï² of such composites decreases suddenly by several orders of magnitude at a critical volume concentration (i.e. Ñ„c=14.27 Vol.%) ,whereas the dielectric constant ï¥ ï‚¢ and the A.C electrical conductivity AC ï³ of such composites increase suddenly at a critical volume concentration (i.e. Ñ„c=14.27 Vol.%).For volume filler content lower than percolation threshold Ñ„ Ñ„c there is increase in the value of their resistivity, and decrease in the value of their dielectric constant and the A.C electrical conductivity AC ï³ with increasing temperature indicating metallic-conduction.